1984
DOI: 10.1093/ajcn/39.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protein quality of an isolated soy protein in young men: relative nitrogen requirements and effect of methionine supplementation

Abstract: The protein nutritional value of an isolated soy protein (Supro-620) was evaluated in a series of nitrogen balance studies in healthy young male MIT students. Experiment 1 involved giving eight subjects graded intakes of the isolated soy protein while seven additional subjects received egg protein. Mean nitrogen intake required for N balance for the isolated soy protein and the egg protein were not significantly different (p greater than 0.1). In experiment 2, nine subjects received soy and the effects on N ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
4
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
0
21
4
1
Order By: Relevance
“…Previous work showing that nitrogen balance is attainable with long-term diets containing moderate amounts of soy [35] would appear to be incongruent with our data; however, these data [35] are confounded by weight loss in a number of the subjects and due to the age of subjects in this study not being entirely comparable. Our data would, in contrast to previous conclusions regarding the adequacy of soy protein [35][36][37], suggest that long-term consumption of soy protein may not attenuate sarcopenic muscle loss.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work showing that nitrogen balance is attainable with long-term diets containing moderate amounts of soy [35] would appear to be incongruent with our data; however, these data [35] are confounded by weight loss in a number of the subjects and due to the age of subjects in this study not being entirely comparable. Our data would, in contrast to previous conclusions regarding the adequacy of soy protein [35][36][37], suggest that long-term consumption of soy protein may not attenuate sarcopenic muscle loss.…”
Section: Discussioncontrasting
confidence: 99%
“…As stated in a recent balance study 'because N balances are sensitive to various factors.. . particularly the level of energy intake and body energy balance, it is not feasible to compare more extensively the present results with those obtained earlier' (Young et al 1984).…”
Section: The Problem Of Selection Of 'Representative' Studiescontrasting
confidence: 53%
“…However, the deviations and the slopes or Y intercepts of the regression lines relating nitrogen balance to nitrogen intake for SPI alone and in combination with rice and egg protein were not significantly different . Moreover, Scrimshaw and Young (12) did not observe any difference in the protein qualities of SPI and milk protein, and Young et al (14) recently reported that the N requirement of SPI for nitrogen equilibrium did not differ significantly from that of egg protein in male subjects and that supplementation of methionine had no effect on the nitrogen balance when the nitrogen intake level was 128mg N/kg/day , but did so at a level of 82mg N/kg/day. Thus, further investigations are required on the protein quality of SPI and its limiting amino acids in humans.…”
Section: Discussionmentioning
confidence: 95%